Furnishing the Shop: The Material Culture of Apothecaries in Britain and the Atlantic World (c.1617-1815) - Booth, Christopher M (2022)
This thesis examines the material culture evidence for the apothecary shops of Britain, Ireland, and British North America between 1617 when the Society of Apothecaries of London was founded and 1815 when the Apothecaries Act made the apothecary a general practitioner of medicine. Given their ubiquity, and the centrality of material culture to both their medical practice and retail spaces, a thorough material assessment of apothecaries is a notable gap in the historiography of the seventeenth and eighteenth centuries which this important interdisciplinary thesis fills.